Diazotizable arylamine cellulose papers for the coupling and hybridization of nucleic acids. - Seed, B (1982)
We describe the synthesis of a family of arylamine-substituted papers which can be diazotized and coupled with nucleic acids. The synthesis is simple and uses readily obtainable starting materials. A partial characterization of the nucleic acid binding activity is reported, as well as a demonstration of the utility of the activated paper for the detection of electrophoretically separated RNA by blot transfer and hybridization.